Anatomical Changes Due to Crude Oil Pollution and its Heavy Metals Component in Three Mucuna Species - A.A. Markson, G.Omosun, H.O. Edeoga (Recent Research in Science and Technology, 2009)
The micromorphological response of three Mucuna species in crude oil polluted soil was investigated. This experiment was a factorial (3 x 5) arrangement in a completely randomized design. Factors and levels were three species of Mucuna (M. veracruz, M. jaspodea and M. ghana) and crude oil concentrations (volume/weight) in the soil (0 %, 1 %, 2 %, 3 %, and 4%). The Mucuna species grown in higher concentrations of crude oil provoked soils (3 - 4 %) exhibited greater sinuosity in their epidermal cell walls than those grown in 0 – 1% oil concentrated soils. The stomatal frequency progressively decreased as the oil concentration increased in soil. Cortical parenchyma cells of stems and roots of the three Mucuna species in higher oil polluted soils were flattened tangentially, smaller in size and had reduced intercellular air spaces. Those plants in control soils had large round polygonal cells. Presence of oil droplets on trichomes of leaves was noticed. Also dotted depositions of oil were noticed in the ground tissues, especially around the vascular bundles. The changes in vegetative anatomy of the three Mucuna species in response to crude oil pollution and its heavy metal components were discussed as a possible use in phytomonitoring of crude oil pollution.